Research on the incentive mechanism of trusted transactions based on blockchain - ZHANG Guiyu; LIU Bowen; LIANG Xiaochen; ZHANG Xiaoyan; LYU Chengjin; YU Sijia; LI Shuo (网络与信息安全学报)
With the development of cloud-network resource transaction technology based on smart contracts, computing power transactions have reached a multi-party scale, seriously affecting the efficiency and credibility of computing network resource transactions. To meet the requirements of trusted transactions and efficient resource incentives in the scenario of multi-party participation in computing network resources, a blockchain-based trusted identity authentication and resource transaction incentive mechanism for computing network resources was designed. The mechanism adopted a distributed authentication strategy based on the reliability of user identity information of the computing network and constructed a trusted transaction entrustment certificate through the authorization of an impartial agency, realizing the trusted implementation of resource transaction tasks. In addition, the application of the transaction incentive mechanism based on contract theory in the trusted transaction and efficient service of computing network resources was discussed. The mechanism was compared with linear incentive and trust incentive models, and the resource utility income and social welfare of the computing network participants were compared. The multi-party optimal utility benefit incentive was verified to measure the incentive efficiency of the mechanism. It proved the effectiveness of the resource transaction incentive mechanism in the transaction verification scenario and effectively ensured the trusted transaction and efficient incentive of computing network resources accessed by multiple service parties. Experimental results show that the proposed transaction mechanism could ensure the credibility, verifiability, and stability of multi-party computing network user transactions. The proposed mechanism is superior to the traditional transaction incentive mechanism in terms of resource transaction efficiency and social welfare benefits.